2016
DOI: 10.1038/bjc.2016.229
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of neuroendocrine malignancies to identify prognostic and therapeutic markers: a Fox Chase Cancer Center Pilot Study

Abstract: Background:The rarity of neuroendocrine malignancies limits the ability to develop new therapies and thus a better understanding of the underlying biology is critical.Methods:Through a prospective, IRB-approved protocol, patients with neuroendocrine malignancies underwent next-generation sequencing of their tumours to detect somatic mutations (SMs) in 50 cancer-related genes. Clinicopathologic correlation was made among poorly differentiated neuroendocrine carcinomas (NECs/poorly differentiated histology and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 31 publications
3
106
0
Order By: Relevance
“…Two studies using nextgeneration sequencing (NGS) revealed alterations; among those, MEN1 and ATRX/DAXX alterations were the most frequent ones ( (Tang et al 2016). Two additional studies (Kimura et al 2016, Vijayvergia et al 2016) confirmed mutations in KRAS and TP53. PHLDA3, a pleckstrin homology-like protein, which is a potent inhibitor of AKT activation (Kawase et al 2009), is inactivated in 72% of pNET patients due to PHLDA3 gene loss of heterozygosity (Ohki et al 2014).…”
Section: Pancreatic Neuroendocrine Tumors (Pnet)mentioning
confidence: 96%
See 1 more Smart Citation
“…Two studies using nextgeneration sequencing (NGS) revealed alterations; among those, MEN1 and ATRX/DAXX alterations were the most frequent ones ( (Tang et al 2016). Two additional studies (Kimura et al 2016, Vijayvergia et al 2016) confirmed mutations in KRAS and TP53. PHLDA3, a pleckstrin homology-like protein, which is a potent inhibitor of AKT activation (Kawase et al 2009), is inactivated in 72% of pNET patients due to PHLDA3 gene loss of heterozygosity (Ohki et al 2014).…”
Section: Pancreatic Neuroendocrine Tumors (Pnet)mentioning
confidence: 96%
“…Three publications reported low-frequency KRAS mutations (10-20%) also in pNET (Yuan et al 2014, Vijayvergia et al 2016, Kimura et al 2016. Although targeting RAS directly is a mission impossible (Cox et al 2014), new options arouse from targeting RAS downstream effectors and cell cycle checkpoint control.…”
Section: Impact Of Genomic Profiling On Therapymentioning
confidence: 99%
“…Loss of retinoblastoma (Rb) and mutations of Kirsten rat sarcoma viral oncogene homolog ( KRAS ) have been recently reported in 55% and 49% of patients with pNECs, in whom such molecular alterations seem to predict response to platinum‐based chemotherapy . Overall, the frequency of mutations is substantially higher in NECs than in NETs …”
Section: Molecular Geneticsmentioning
confidence: 99%
“…In addition, mutations may increase tumor antigenicity, and the mutational load may predict response of tumors to immunotherapy [34,35,36]. In contrast to carcinoid tumors [34], NECs show a higher mutational frequency [37,38], suggesting that high-grade NENs may be a preferred target of immunotherapy.…”
Section: Immune Checkpoint Inhibitionmentioning
confidence: 99%